Development of Geopolymer Concrete with Different Curing Conditions - Nuruddin, M.F. Nuruddin; Kusbiantoro, A. Kusbiantoro; Qazi, S. Qazi; Darmawan, M.S. Darmawan; Husin, N.A. Husin (IPTEK The Journal for Technology and Science, 2011)
Environmental issues resulted from cement production have become a major concern today. To develop a sustainable future it is encouraged to limit the use of this construction material that can affect the environment. Cement replacement material was proposed to partially replace cement portion in concrete. Geopolymer is a part of inorganic polymer material that has similar bonding function like cement in concrete. It consists of alkaline solutions and geological source material. Alkaline liquids used in this research are 8 M sodium hydroxide (NaOH) solution and sodium silicate (Na2SiO3) solutions, while source materials are fly ash and microwave incinerated rice husk ash (MIRHA). Three different curing regimes, namely hot gunny curing, ambient curing, and external exposure curing, were applied to obtain suitable method that was suitable with cast in situ application. Geopolymer concrete samples were tested on their compressive strength and microstructure properties. It was found that external exposure curing had the highest compressive strength compared to other two curing methods. Scanning electron microscopy analysis also showed better improvement in interfacial transition zone for concrete sample with external exposure curing.